Evolutionary Relationships and Divergence of KNOTTED1-Like Family Genes Involved in Salt Tolerance and Development in Cotton (Gossypium hirsutum L.) - Zhang, Xiaohong; Zhao, Junjie; Wu, Xiangyuan; Hu, Genhai; Fan, Shuli; Ma, Qifeng (Frontiers in Plant Science, 2021)
The KNOX (KNOTTED1-like homeobox) transcription factors play an important role in leaf, shoot apical meristem and seed development and respond to plant biotic and abiotic stresses. In this study, we analyzed KNOX gene family of polyploid cotton, which has a subsequent evolutionary history. A total of 44 putative KNOX genes identified in Gossypium hirsutum. All KNOX genes from nine higher plant species were classified into four clades based on a phylogenetic analysis and on the conserved gene structural features. Chromosomal localization and collinearity analysis suggested that no tandem duplication, whole-genome duplication, and a polyploidy event contributed to the expansion of the cotton KNOX gene family. Analyses of expression profiles and artificial selection revealed that the GhKNOX genes likely responded to diverse stresses and involved in cotton fiber developmental processes. Silencing of GhKNOX2-A promoted the salt tolerance of cotton seeding, while silencing GhKNOX10-A and GhKNOX14-A reduced the cotton seeding tolerance to salt stress. Silencing GhSTM3-A/D may influenced the cotton flowering time and plant development. These findings may clarify the evolution of cotton KNOX gene family and may provide a foundation for future functional studies of KNOX proteins regarding cotton growth development and responses to abiotic stresses.